"An act for preventing Negroes Insurrections," 2 W.W. Hening, Laws of Va. from First Sess. of Legis. in 1619, Act 10 at 481 (1823) - (:unkn) unknown (My University, 1680)
"No negro, or enacted by the kings most excellent majestie by and with other slave to the consent of the generall assembly, and it is hereby carry arms, of enacted by the authority aforesaid, that from and after fensive: the publication of this law, it shall not be lawfull for any negroe or other slave to carry or arme himselfe with any club, staffe, gunn, sword or any other weapon of defence or offence..."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES